Adipose‐derived stem cells and the stromal vascular fraction in polyglycolic acid‐collagen nerve conduits promote rat facial nerve regeneration. Issue 6 (25th October 2018) - Shimizu, Mari; Matsumine, Hajime; Osaki, Hironobu; Ueta, Yoshifumi; Tsunoda, Satoshi; Kamei, Wataru; Hashimoto, Kazuki; Niimi, Yosuke; Watanabe, Yorikatsu; Miyata, Mariko; Sakurai, Hiroyuki
Abstract: Adipose‐derived stem cells (ADSCs) and the stromal vascular fraction (SVF) promote nerve regeneration. Biodegradable nerve conduits are used to treat peripheral nerve injuries, but their efficiencies are lower than those of autologous nerve grafts. This study developed biodegradable nerve conduits containing ADSCs and SVF and evaluated their facial nerve regenerating abilities in a rat model with a 7‐mm nerve defect. SVF and ADSCs were individually poured into nerve conduits with polyglycolic acid‐type I collagen as a scaffold (ADSCs and SVF groups). The conduits were grafted on to the nerve defects. As the control, the defect was bridged with polyglycolic acid‐collagen nerve conduits without cells. At 13 weeks, after transplantation, the regenerated nerves were evaluated physiologically and histologically. The compound muscle action potential of the SVF group was significantly higher in amplitude than that of the control group. Electron microscopy showed that the axon diameter of the SVF group was the largest, followed by the ADSC group and control group with significant differences among them. The SVF group had the largest fiber diameter, followed by the ADSC group and control group with significant differences among them. The ADSC group had the highest myelin thickness, followed by the SVF group and control group with significant differences among them. Identical excellent promoting effects on nerve regeneration were observed in both the ADSC and SVF groups. Using SVF in conduits was more practical than using ADSCs because only the enzymatic process was required to prepare SVF, indicating that SVF could be more suitable to induce nerve regeneration.